Epidemiology, Clinical Features, and Genetics of Multiple Endocrine Neoplasia Type 2B in a Complete Population. (29th October 2014) - Znaczko, Anna; Donnelly, Deirdre E.; Morrison, Patrick J.
Abstract : This paper reports the first published prevalence of Multiple endocrine neoplasia type 2B (MEN 2B). Estimates of the epidemiology of MEN 2B were based on a single population with one centralized genetic clinic. MEN 2B remains a relatively rare condition and can be easily missed if the diagnosis has not been considered.